Comparative Leaf Epidermal Anatomy of Tribe Ruellieae (Acanthaceae) in Northeastern Thailand - Khonkayan, Sutarat; Jonsonchai, Sudarat; Namang, Saksit (Science Essence Journal, 2019)
บทคัดย่อ ศึกษาลักษณะกายวิภาคศาสตร์เนื้อเยื่อชั้นผิวใบของพืชเผ่า Ruellieae วงศ์ Acanthaceae จำนวน 12 สกุล 16 ชนิด ได้แก่ สกุล Barleria L. 3 ชนิด สกุล Justicia L. และ Pseuderanthemum <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=83927-3&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DPseuderanthemum%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Radlk. สกุลละ 2 ชนิด และสกุล Andrographis <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=115961-3&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DAndrographis%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Wall. ex Nees, Asystasia <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=154559-3&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DAsystasia%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Blume, Clinacanthus <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=479-1&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DClinacanthus%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Nees, Eranthemum L., Phlogacanthus <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=479-1&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DClinacanthus%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Nees, Rhinacanthus <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=479-1&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DClinacanthus%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Nees, Ruellia L., Strobilanthes <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=154559-3&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DAsystasia%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">Blume และ Thysanostigma <a href="http://www.ipni.org/ipni/idPlantNameSearch.do?id=1004-1&back_page=%2Fipni%2FeditAdvPlantNameSearch.do%3Ffind_infragenus%3D%26find_isAPNIRecord%3Dtrue%26find_geoUnit%3D%26find_includePublicationAuthors%3Dtrue%26find_addedSince%3D%26find_family%3Dacanthaceae%26find_genus%3DThysanostigma%26find_sortByFamily%3Dtrue%26find_isGCIRecord%3Dtrue%26find_infrafamily%3D%26find_rankToReturn%3Dall%26find_publicationTitle%3D%26find_authorAbbrev%3D%26find_infraspecies%3D%26find_includeBasionymAuthors%3Dtrue%26find_modifiedSince%3D%26find_isIKRecord%3Dtrue%26find_species%3D%26output_format%3Dnormal">J.B.Imlay สกุลละ 1 ชนิด โดยนำตัวอย่างมาลอกผิวใบและย้อมด้วยสีซาฟรานิน 1% ที่ละลายในน้ำ พบว่าลักษณะกายวิภาคของแผ่นใบที่สามารถใช้ในการระบุชนิดพืชที่ศึกษาได้ คือ รูปร่างและผนังเซลล์ในเนื้อเยื่อชั้นผิว ชนิดของไทรโคม การมีหรือไม่มีผลึกหินปูนที่สะสมในเซลล์ ช่องสารหลั่งและสารแทนนิน ในการศึกษาครั้งนี้มีพืชเผ่า Ruellieae 4 ชนิด ที่มีการศึกษากายวิภาคศาสตร์ผิวใบเป็นครั้งแรก คำสำคัญ: กายวิภาคศาสตร์ เนื้อเยื่อชั้นผิวใบ พืชเผ่า Ruellieae ABSTRACT The leaf epidermal characteristics of 12 genera 16 species of the tribe Ruellieae, family Acanthaceae i.e., 3 species each of Barleria L. 2 species of each Justicia L. and Pseuderanthemum Radlk. and 1 species each of Andrographis Wall. ex Nees, Asystasia Blume, Clinacanthus Nees, Eranthemum L., Phlogacanthus Nees, Rhinacanthus Nees, Ruellia L., Strobilanthes Blume and Thysanostigma J. B. Imlay were studied. The samples were investigated by leaf epidermal peeling and staining with 1% safranin in water. The results showed that epidermal cell shape and cell wall, type of trichome, presence or absence of cystolith, secretory cavities and tannin were useful characters for identification of the studied species. Information of leaf surface anatomy for 4 species in the tribe Ruellieae were firstly provided here. Keywords: Anatomy, Epidermis, Ruellieae